Arctic greening and browning: Challenges and a cascade of complexities - Phoenix, Gareth K.; Treharne, Rachael (Global change biology, 2022)
Arctic greening (the increase in plant biomass and productivity at high latitudes) is one of the clearest large‐scale vegetation changes seen in recent decades. However, despite being the subject of considerable research effort, our understanding of this phenomenon is far from complete. Challenges around remote sensing, process based understanding, and the spatial and temporal heterogeneity of greening—including the opposite process of Arctic browning—challenges our ability to model and predict Arctic vegetation change and its biogeochemical consequences.